2015
DOI: 10.4172/2329-6879.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders Among Self Employed Sewing Machine Operators in Maiduguri, Nigeria

Abstract: Background: Globally, studies on prevalence of WMSDs focused mainly on populations in organized industrial sectors and professions.Purpose: This study was therefore designed to determine the prevalence of WMSDs, risk factors and coping strategies for this disorder among self-employed sewing machine operators in Maiduguri, Nigeria.Method: Close-ended structured questionnaire, drafted and modified from the short version of the standardized Nordic Musculoskeletal Questionnaire (NMQ) for investigating work-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The multivariable regression model demonstrated that age was a markedly contributing factor for the development of upper extremity disorders. This result was in agreement with the other studies [2, 19, 38, 41, 42]. The probable explanation for these similarities is due to the fact that the biological/functional structures of human body, particularly those related to supportive structures, like muscles, joints, nerves, ligaments, and tendons, would tend to degenerate as age of the workers increases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The multivariable regression model demonstrated that age was a markedly contributing factor for the development of upper extremity disorders. This result was in agreement with the other studies [2, 19, 38, 41, 42]. The probable explanation for these similarities is due to the fact that the biological/functional structures of human body, particularly those related to supportive structures, like muscles, joints, nerves, ligaments, and tendons, would tend to degenerate as age of the workers increases.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, out of the total indicated disorders of upper body regions, about 38.8% were related to upper back pain, 32.4% to wrists/hand disorders, 29.3% to the neck and elbow/forearm each, and 27.1% ( N =113) to the shoulder. This result was relatively comparable with a study in Nigeria (34.7%) [38]. The comparable reports might be due to the reason that workplace illness reporting and management procedures relatively resemble in the developing countries.…”
Section: Discussionsupporting
confidence: 86%